BS ISO 15930-9. Graphic technology. Prepress digital data exchange using PDF. Part 9. Complete exchange of printing data (PDF/X-6) and partial exchange of printing data with external profile reference (PDF/X-6p and PDF/X-6n) using PDF 2.0 (17th March 2020) - British Standards Institution,
No abstract available